KONSEP PERLAKUAN KHUSUS DAN BERBEDA SETELAH KONFERENSI BUENOS AIRES DAN DAMPAKNYA BAGI PERIKANAN SKALA KECIL DI INDONESIA - Nur, Muhammad; Susanto, M.Hajir (Varia Justicia, 2019)
The WTO Conference held in Hong Kong in 2005 agreed that subsidies must be immediately abolished by each WTO member country. But the decision was not approved by many countries, especially developing countries and less developed countries, so the concept of Special and Differential Treatment appears. The purpose of this paper is to analyze the extent of this idea's impact on the small-scale fisheries in Indonesia after the Buenos Aires Conference. a normative juridical research method is used by authors that examining library materials and other secondary materials. The author uses the data collection method by the literature study. Documents in the form of primary legal materials, secondary legal materials, and non-legal materials are used in this paper. At the Ministerial Meeting in Buenos Aires in 2017 Special and Differential Treatment Concept was discussed. The result of this study found that regarding of conclusion in the 11th Ministerial Conference in Buenos Aires, Indonesia has a chance to protect their small-scale fisheries interest to continue to provide subsidies in the field of fisheries. However, Indonesia still has a lot of work to be done to develop disciplines of fisheries subsidies within the framework of cooperation at the WTO and prevent the misuse of subsidies provided.